Maternal ability to correctly detect significant jaundice in Indian neonates - Alok Yadav; Amit Devgan; Subhash Chandra Shaw; Puja Dudeja (Wolters Kluwer Medknow Publications, 2020)
Background: The ability of mothers to correctly detect jaundice in their newborns is largely unknown. The objective was to ascertain the ability of mother to correctly detect the presence of significant jaundice in her newborn. Materials and Methods: This cross-sectional study was conducted in a tertiary care hospital in eastern India from February 2015 to July 2016. All inborn neonates more than 34 weeks' gestation were included. Congenital malformations, perinatal asphyxia, neonatal sepsis, readmission after discharge, and isoimmunization were excluded. A total of 505 inborn newborns were independently assessed by the mother and the treating pediatrician for significant jaundice every day till discharge. Each newborn underwent total serum bilirubin estimation on suspicion of significant jaundice by either of the two or at discharge, whichever was earlier. Results: The sensitivity, specificity, positive predictive value (PPV), and negative predictive value of maternal detection of significant jaundice was 51.47%, 88.33%, 39.29%, and 92.12%, respectively. Conclusion: Mothers have poor sensitivity and PPV to detect significant neonatal jaundice in the Indian population.